Boost Your Digital Portfolio: From Linkedin Profile to Github Repository - Fizar, Bintang Al; Fakhul Jannah, Elsa Ananda Hanifah; Zahro, Rahmita; Vivria, Muhammad Efendi; Sutrisno, Mirza; Adharani, Yana; Mujiastuti, Rully; Rosanti, Nurvelly (Society : Jurnal Pengabdian Masyarakat, 2025)
In the modern era, having a digital portfolio is an important requirement for students and aspiring professionals in the field of technology. To support this, LinkedIn profile management and project publication to GitHub are strategies that can be applied. The activity themed "Boost Your Digital Portfolio: From LinkedIn Profile to GitHub Repository" was held to equip participants with this understanding and skills. The activity consisted of two sessions: a webinar that discussed the preparation of LinkedIn profiles and the use of GitHub as a medium for project publication, and a workshop that focused on developing a template-based portfolio website and publication to the GitHub repository. Evaluation was conducted through a feedback questionnaire. The results showed that 47.9% of participants were satisfied and 48.1% were very satisfied. This shows that the majority of participants gave a positive response to the material, resource persons, and the overall implementation of the activity.